C programming for the absolute beginner - Davenport, Keith; Vine, Michael (Cengage Learning, 2015)
Are you an aspiring computer programmer? This title guides you, step-by-step, through C programming with clear explanations and plenty of examples and illustrations. Each chapter includes a simple, fully functional game project that will test your new programming knowledge and let you put your skills to work